Hubungan antara Anemia dengan Kejadian Ketuban Pecah Dini di Rumah Sakit Sanjiwani Tahun 2020 - Sintya Sevadani; Asri Lestarini; Anak Agung Gede Raka Budayasa (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
Prelabor rupture of membranes (PROM) is a condition rupture of the membranes before the time of labor. The prevalence of PROM that occurs in Indonesia is still high. Anemia as one of the factors causing PROM. The purpose of this study to determine the relationship between anemia and the incidence of prelabor rupture of membranes at the Sanjiwani Hospital in 2020. This study used a cross-sectional and using secondary data from medical records from January 2020-December 2020. The study sample size was 96 samples obtained using the consecutive sampling method. Data analysis was carried out univariate and bivariate with chi-square test with a significance level (Î±) of 0.05. The data will be analyzed using SPSS. The result of this study obtained the number of prevalence of PROM in pregnant women with anemia is 26,9 with a significance level is 0,412. The result of this study is that there is no significant relationship between anemia and the incidence of prelabor rupture of membranes at the Sanjiwani Hospital in 2020. A non significant result can occur because the antenatal care (ANC) carried out by the mother during pregnancy has been good. Pregnant women are expected to carry out ANC properly to prevent anemia. Keywords: Premature rupture of membranes, Anemia, Sanjiwani Hospital